2021
DOI: 10.3390/diagnostics11020241
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing-Based Framework for Breast Cancer Diagnosis Using Extreme Learning Machine

Abstract: Globally, breast cancer is one of the most significant causes of death among women. Early detection accompanied by prompt treatment can reduce the risk of death due to breast cancer. Currently, machine learning in cloud computing plays a pivotal role in disease diagnosis, but predominantly among the people living in remote areas where medical facilities are scarce. Diagnosis systems based on machine learning act as secondary readers and assist radiologists in the proper diagnosis of diseases, whereas cloud-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 71 publications
1
69
0
Order By: Relevance
“…These studies suggested a method to protect sensor data and enhances the performance of big-data analysis in the system. Dynamic and adaptive optimization heuristics, such as genetic algorithm and reinforcement aware schemes, were suggested [2,5,23,[25][26][27]. The different objectives were obtained, such as the cost, security, response time and energy of sensors devices during offloading and scheduling in the IoMT network.…”
Section: Related Workmentioning
confidence: 99%
“…These studies suggested a method to protect sensor data and enhances the performance of big-data analysis in the system. Dynamic and adaptive optimization heuristics, such as genetic algorithm and reinforcement aware schemes, were suggested [2,5,23,[25][26][27]. The different objectives were obtained, such as the cost, security, response time and energy of sensors devices during offloading and scheduling in the IoMT network.…”
Section: Related Workmentioning
confidence: 99%
“…A distance-based computation is done for internal markers and morphological dilation was applied for the external marker. In recent times authors in [ 15 ] presented an extreme learning machine (ELM) model for the prognosis of breast cancer. In addition, a gain ratio feature selection method is deployed to remove insignificant features.…”
Section: Related Workmentioning
confidence: 99%
“…Recurrent Neural Network (R.N.N.) can attach hidden layers and previous ones circularly [40][41][42][43][44][45][46][47][48]. These R.N.N.…”
Section: Fuzzy Weight Based Recurrent Neural Network (Fwrnn)mentioning
confidence: 99%